2015
DOI: 10.1177/1750635215611610
|View full text |Cite
|
Sign up to set email alerts
|

Fighting, worrying and sharing: Operation ‘Protective Edge’ as the first WhatsApp war

Abstract: This study looks at the roles that WhatsApp, the popular smartphone application, played in the lives of Israeli citizens, who were exposed to war menaces during July 2014. During the war, WhatsApp became the subject of public, media, and political discourse, especially within the context of disseminating information related to combat – ‘authentic’ news items (before they were published in the media) alongside rumors that were devoid of factual basis. Research questions focused on the ways in which citizens use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 31 publications
0
43
0
2
Order By: Relevance
“…The study is limited by the fact that it examined press coverage and audience reception; it did not examine actual social media uses but rather their framing in the mainstream media. Hence, it is certainly possible that Facebook and WhatsApp campaigns for the residents of the South, soldiers, or their families gained significant public attention, and that satirical memes were also quite salient on Facebook and WhatsApp during the war (Malka et al, 2015). Such topics that reached a high place in the public's mind could not find a way to a respectable place in the agenda of the mainstream media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study is limited by the fact that it examined press coverage and audience reception; it did not examine actual social media uses but rather their framing in the mainstream media. Hence, it is certainly possible that Facebook and WhatsApp campaigns for the residents of the South, soldiers, or their families gained significant public attention, and that satirical memes were also quite salient on Facebook and WhatsApp during the war (Malka et al, 2015). Such topics that reached a high place in the public's mind could not find a way to a respectable place in the agenda of the mainstream media.…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey of the Israel Internet Society (2014), 39% of WhatsApp users learned through it about security events before they were publicized, while 37% confirmed that they forwarded classified information received through WhatsApp. Another study of Malka, Ariel, and Avidar (2015) conducted via a representative online panel indicates that 47% of Israelis used WhatsApp at least once a day to keep up with what was going on and over 36% did so several times a day. Overall, 38% reported they were involved in forwarding rumors at least once during the war.…”
Section: The Israel-gaza War Of 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…WhatsApp is used not only for exchanging information, but also for entertainment, and to keep in touch with friends and family (Malka, Ariel, & Avidar, 2015). Some (e.g., O'Hara, Massimi, Harper, Rubens, & Morris, 2014) view the motivation to use the application as stemming from its phatic function, that is, a desire to dwell with friends in an uninterrupted, open space of communication, even without exchanging important information.…”
Section: Whatsapp: Features Of a Communication Mediummentioning
confidence: 99%
“…It facilitates interactive, multimedia discourse with quick exchanges of text, images, audio, and video on people's mobile phones. WhatsApp's popularity has been attributed to the fact that it imitates face-to-face communication best and to the sense of immediacy it affords, as messages synchronously flow between group members (Malka, Ariel, & Avidar, 2015). WhatsApp groups functions as "micro communities" (Karapanos, Teixeira & Gouveia, 2016) and establish a sense of community space, where informal communication takes place between the members of the closed group.…”
Section: Whatsapp: Features Of a Communication Mediummentioning
confidence: 99%